Brazilian Society of Otology task force : cochlear implant : recommendations based on strength of evidence - Tsuji, Robinson Koji (2025)
Objective: To make evidence-based recommendations for the indications and complications of Cochlear Implant (CI) surgery in adults and children. Methods: Task force members were educated on knowledge synthesis methods, including electronic database search, review and selection of relevant citations, and critical appraisal of selected studies. Articles written in English or Portuguese on cochlear implantation were eligible for inclusion. The American College of Physicians’ guideline grading system and the American Thyroid Association’s guideline criteria were used for critical appraisal of evidence and recommendations for therapeutic interventions. Results: The topics were divided into 2 parts: (1) Evaluation of candidate patients and indications for CI surgery; (2) CI surgery - techniques and complications. Conclusions: CI is a safe device for auditory rehabilitation of patients with severe-to-profound hearing loss. In recent years, indications for unilateral hearing loss and vestibular schwannoma have been expanded, with encouraging results. However, for a successful surgery, commitment of family members and patients in the hearing rehabilitation process is essential.